Synthesis, FT–IR characterization and crystal structure of aqua(5,10,15,20-tetraphenylporphyrinato-κ(4) N)manganese(III) trifluoromethanesulfonate - Harhouri, Wafa (Acta Crystallogr E Crystallogr Commun, 2016)
In the title salt, [Mn(C(44)H(28)N(4))(H(2)O)](CF(3)SO(3)) or [Mn(III)(TPP)(H(2)O)](CF(3)SO(3)) (where TPP is the dianion of 5,10,15,20-tetraphenylporphyrin), the Mn(III) cation is chelated by the four pyrrole N atoms of the porphyrinate anion and additionally coordinated by an aqua ligand in an apical site, completing the distorted square-pyramidal coordination environment. The average Mn—N(pyrrole) bond length is 1.998 (9) Å and the Mn—O(aqua) bond length is 2.1057 (15) Å. The central Mn(III) ion is displaced by 0.1575 (5) Å from the N(4)C(20) mean plane of the porphyrinate anion towards the apical aqua ligand. The porphyrinate macrocycle exhibits a moderate ruffling and strong saddle deformations. In the crystal lattice, the [Mn(III)(TPP)(H(2)O)](+) cation and the trifluoromethanesulfonate counter-ions are arranged in alternating planes packed along [001]. The components are linked together through O—H⋯O hydrogen bonds and much weaker C—H⋯O and C—H⋯F interactions. The crystal packing is further stabilized by weak C—H⋯π interactions involving the pyrrole and phenyl rings of the porphyrin moieties.